2014
DOI: 10.1097/icl.0000000000000081
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Cross-Linking of the Boston Keratoprosthesis Donor Carrier to Prevent Corneal Melting in High-Risk Patients

Abstract: Collagen crosslinking was previously shown to halt the enzymatic degradation of corneal buttons ex vivo. This study demonstrates the safety and potential benefit of using crosslinked corneal grafts as carriers for the B-KPro, especially in eyes at higher risk of postoperative melt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…In some cases, the implant is then covered by transplanted autologous tissue or eyelid skin (Todani et al, 2011). In order to accommodate the stromal keratocytes, the skirt material should have contiguous voids in the micronmicrometer range for cell integration and maintenance of normal cell-cell contacts (Patel et al, 2006;Robert et al, 2014). However, the posterior surface of the implant should inhibit cellular attachment in order to prevent development of opaque fibrous retroprosthetic membranes (Ament et al, 2009).…”
Section: Biomaterials Designed For Keratoprosthesesmentioning
confidence: 98%
“…In some cases, the implant is then covered by transplanted autologous tissue or eyelid skin (Todani et al, 2011). In order to accommodate the stromal keratocytes, the skirt material should have contiguous voids in the micronmicrometer range for cell integration and maintenance of normal cell-cell contacts (Patel et al, 2006;Robert et al, 2014). However, the posterior surface of the implant should inhibit cellular attachment in order to prevent development of opaque fibrous retroprosthetic membranes (Ament et al, 2009).…”
Section: Biomaterials Designed For Keratoprosthesesmentioning
confidence: 98%
“…In order to reduce postoperative tissue melt, carrier corneas have also been cross-linked with ultraviolet (UV) light which has been shown to convey considerable resistance to enzymatic digestion in vitro [8]. Clinically such corneas have been employed as carriers with success [47,69]. For the developing world, however, less expensive alternatives must be sought when autografts are not possible; experiments with γ-radiated porcine xenografts, supplemented with a total conjunctival flap, and other possibilities are presently ongoing [26].…”
Section: Prognostic Categoriesmentioning
confidence: 99%
“…Robert et al reported on cross-linking of the Boston keratoprosthesis donor carrier to prevent corneal melting in a patient with post KPro corneal melt. The patient maintained his visual acuity and showed no evidence of corneal thinning or melt in the first postoperative year [ 141 ].…”
Section: Other Applications Of Cross-linkingmentioning
confidence: 99%